Peranan K3 dalam Pelaksanaan Pembangunan Perpipaan Air Limbah Kota Makassar Zona Barat Laut - Afifa, Witri Aulia (Program Studi Teknik Sipil Universitas Bosowa, 2023)
This study aims to determine the role of discipline, technology, and the environment on the performance of the implementation of the waste water pipeline development of Makassar City in the northwest zone and to determine the variables that have a large role in performance. This research is a type of quantitative research that underlies taking data, determining variables and then measuring with numbers so that analysis can be carried out according to statistical procedures. Based on the research results, the results that most significantly affect the performance of the Makassar City Northwest Zone wastewater piping construction project are discipline, technology, and environmental variables.Based on the results of the analysis value showing the environmental variable (comparison of the value of t_count with t_table, the results shown are the value of t_count > t_table (4,639 > 1,674) then the role of K3 in influencing the implementation of the waste water piping construction of Makassar City in the northwest zone is 45%